Nonisothermal Degradation Kinetics and Life Prediction of the Pendent Phenyl-Containing Polyarylate. Issue 1 (2nd January 2017) - Liu, Pengqing; Xu, Jianjun
ABSTRACT: The nonisothermal degradation kinetics of a pendent phenyl-containing polyarylate (PAR-P)were studied using different kinetic models, including the Kissinger method, Flynn–Wall–Ozawa (FWO) method, and Coats–Redfern (CR) method. The "three kinetic factors" of degradation, namely, activation energy ( E ), pre-exponential factor ( A ), and the reaction mechanism function ( f (α)) were determined by these methods. Moreover, the lifetime equations of PAR-P were deduced, and its lifetime was predicted. The Kissinger method could be used to describe the nonisothermal degradation of PAR-P, and the results indicated that PAR-P could be degraded more easily in air than in nitrogen. The FWO method was expected to give more reliable values of the activation energy (209.71 kJ·mol −1 in nitrogen and 176.22 kJ·mol −1 in air) due to not having to introduce the reaction mechanism function during the calculation. According to the results of the CR method, the thermal degradation reaction mechanism was probably the R1 model in nitrogen, while it was likely to be the F2 model in air. The long-term and short-term use temperatures of PAR-P in air were 260°C and 300°C, respectively. The lifetime of PAR-P in nitrogen was much longer than that in air at low temperature, but had little difference when the use temperature exceeded 260°C. Although the lifetime of PAR-P obtained from the present work was unrealistic due to probable contributions from other unconsidered factors and being determined by a single factor method, it still could play a guiding role for designing the structure and determining the use conditions of the material.